(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
Recently there is an increased concern for the development of not only well-designed but also sustainable materials. Material sustainability is associated with the extraction of renewable resources and disposal procedures that would not injure our ecosystem. In this respect, indigenous agricultural wastes or by-products are suitable alternatives to lightweight and disposable green-materials at low cost. Agro-waste and biomass materials are plentiful in many parts of the world including Malaysia. Fibers obtained from agricultural by-products are often used as fillers or reinforcement in non-biodegradable polymer matrix. Polylactic acid (PLA), which is a compostable and biodegradable thermoplastic, is derived from renewable agro-sources such as potato, corn, or sugarcane. The mechanical and thermal properties of select biofibers-filled PLA composites are comparable to that of the composites made from conventional fibers. Research findings imply the feasibility of processing PLA with natural fibers such as kenaf using existing manufacturing technologies. Natural fiber filled biodegradable polymer composite materials have the advantage of simple and safe disposal over petroleum-based polymers besides generating new low-carbon economy for the plantation sector. However, research outcomes show that the fiber/matrix interface of PLA and natural fiber is weak due to incompatible surface properties of the two material types. In this article, issues pertaining to fiber/matrix interfacial adhesion, potential renewable sources of polymers and processing technologies of natural fiber (or –eco)-biocomposite materials are reviewed. The prospect of replacing traditional polymers obtained from non-renewable fossil resources with biopolymers to develop sustainable eco-biocomposite materials for shock cushioning application such as for packing and packaging materials is discussed in particular.